Glass powder composition, conductive paste containing glass powder composition and preparation method of conductive paste
By using a conductive paste containing a specific glass powder composition in a TBC cell, the problems of smooth surface and small thickness of p+poly silicon are solved, and a good balance between contact performance and metal recombination is achieved, and the efficiency of solar cells is improved. .
Patent Information
- Application Number
- CN202411626355.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-02-21
AI Technical Summary
In TBC batteries, the thickness of p+poly silicon is less than 300nm, resulting in serious damage when the aluminum powder exists, which cannot meet the requirements of contact performance and metal composite. Moreover, due to the smooth surface, better wetting ability and uniform contact points are required. distributed.
A glass powder composition is adopted, comprising a first glass powder and a second glass powder, the first glass powder contains a specific proportion of alkali metal oxide, SiO2, Bi2O3, TeO2, PbO, WO3, MoO3 and ZnO, and the second glass powder Contains a specific proportion of alkali metal oxides, SiO2, Bi2O3, TeO2, PbO, Ag2O, lanthanide compounds, WO3, MoO3 and ZnO, and are used to prepare conductive pastes.
By using the conductive paste of the glass powder composition, a good balance of ohmic contact on p+poly silicon and metal composite performance in TBC cells is achieved, and the efficiency of the solar cell is improved.
Smart Images

Figure BDA0005134839640000171 
Figure BDA0005134839640000181
Abstract
Description
Technical Field
[0001] The invention relates to a glass powder composition, a conductive paste containing the glass powder composition and a preparation method thereof. Background Art
[0002] Solar energy is an attractive green energy source because it is sustainable and only produces non-polluting byproducts, so people have developed solar cells that use the photovoltaic effect to convert solar energy into electrical energy. Solar cells are usually made of semiconductive materials, such as appropriately doped silicon materials. When light shines on the solar cell, a portion of the incident light is reflected by the surface, and the remaining portion of the incident light is transmitted to the solar cell. The transmitted photons are absorbed by the solar cell, which in turn excites the electrons of the semiconductive material to generate electron-hole pairs, and the electrons and holes are guided through the electrodes located on the front side of the substrate (i.e., the side illuminated by light) and the back side (i.e., the side not illuminated by light) to form current, thereby obtaining electrical energy.
[0003] The electrodes in contact with the silicon wafer in the solar cell are usually manufactured by applying a conductive paste to the substrate by screen printing and then sintering the conductive paste. The conductive paste usually contains glass powder, conductive powder and organic carrier. The glass powder corrodes the passivation layer during the sintering process of the conductive paste, so that the conductive powder in the conductive paste forms an ohmic contact with the silicon wafer under the passivation layer after sintering.
[0004] In existing n-type Topcon cells, ohmic contact for the p+ emitter is achieved by adding aluminum powder to the conductive paste. However, in the case of p+poly silicon in TBC cells, since the thickness of p+poly silicon is usually less than 300nm, the presence of aluminum powder will cause serious damage to the p+poly silicon region, resulting in the failure to meet the metal composite requirements even if the contact performance requirements are met, thereby affecting the efficiency of the solar cell. On the other hand, the boron doping concentration of p+poly silicon is usually an order of magnitude lower than the phosphorus doping concentration of n+poly silicon, which makes contact with p+poly silicon more difficult. In addition, unlike the silicon pyramids formed by surface texturing at the p+ emitter of the n-type Topcon cell, the p+poly silicon in the TBC cell has a smoother surface due to etching with an alkaline solution. Therefore, the conductive paste for p+poly silicon requires better wetting ability and a more uniform distribution of contact points to achieve a good balance of performance in both ohmic contact and metal composite.
[0005] Therefore, there is an urgent need in the art for a conductive paste that can be used for p+poly silicon in TBC cells to achieve a good balance between ohmic contact and metal composite. Summary of the invention
[0006] To this end, the present invention provides a glass powder composition, which comprises:
[0007] a) a first glass powder, and
[0008] b) a second glass powder,
[0009] wherein the first glass powder comprises 2-9 wt % of alkali metal oxide, 1-5 wt % of SiO2, 8-20 wt % of Bi2O3, 25-50 wt % of TeO2, 20-45 wt % of PbO, 0-10 wt % of WO3, 0-5 wt % of MoO3 and 0-5 wt % of ZnO, wherein the weight percentages are based on the total weight of all compounds in the first glass powder; and
[0010] The second glass powder contains 5-15 weight % of alkali metal oxides, 5-12 weight % of SiO2, 8-20 weight % of Bi2O3, 20-40 weight % of TeO2, 20-40 weight % of PbO, 0.1-7 weight % of Ag2O, 0.1-7 weight % of lanthanide compounds, 0-10 weight % of WO3, 0-5 weight % of MoO3 and 0-5 weight % of ZnO, wherein the weight percentages are based on the total weight of all compounds in the second glass powder.
[0011] The present invention also provides a conductive paste of p+poly silicon used in a TBC battery, wherein the conductive paste comprises the glass powder composition.
[0012] The present invention also provides an electrode for a crystalline silicon solar cell, which is formed by sintering the conductive paste.
[0013] The present invention also provides a crystalline silicon solar cell, which comprises a substrate and the electrode combined on the substrate.
[0014] The applicant has found that the solar cell prepared by using the conductive paste containing the glass powder composition of the present invention has a good balance of the properties of ohmic contact and metal composite. DETAILED DESCRIPTION
[0015] Conductive paste
[0016] According to the present invention, the conductive paste is applied to the surface of the solar cell wafer and forms a solid electrode in electrical contact with the surface when sintered. According to the present invention, the conductive paste comprises or consists of the following components:
[0017] 80-88% by weight of silver powder,
[0018] 3.5-6 wt% of a glass powder composition, and
[0019] 6-15% by weight of an organic carrier,
[0020] The weight percentages are based on the total weight of the conductive paste.
[0021] Silver powder
[0022] The silver powder present in the conductive paste provides metallic conductivity to the solid electrode formed when the conductive paste is sintered.
[0023] According to the present invention, the silver powder (silver particles) can have various shapes, surfaces, sizes, surface area to volume ratios. Many shapes are known to those skilled in the art. Some examples are spherical, angular, elongated (rod-like or needle-like) and flat (flake-like). Silver powder can also exist as a combination of particles of different shapes. According to the present invention, silver powder having a shape or a combination of shapes that is conducive to favorable sintering, electrical contact, adhesion and conductivity of the prepared electrode is preferred. Without considering the surface characteristics, one way to characterize such shapes is by means of the parameters length, width and thickness. For the purposes of the present invention, the length of a particle is given by the length of the longest spatial displacement vector whose two endpoints are contained within the particle. The width of a particle is given by the length of the longest spatial displacement vector perpendicular to the length vector defined above and whose two endpoints are contained within the particle. The thickness of a particle is given by the length of the longest spatial displacement vector perpendicular to the length vector and width vector defined above and whose two endpoints are contained within the particle. In one embodiment of the present invention, it is preferred to have a silver powder with a shape that is as uniform as possible, i.e. a shape in which the ratios of length, width and thickness are as close to 1 as possible, preferably all ratios are between 0.7 and 1.5, more preferably between 0.8 and 1.3. In one embodiment of the present invention, preferred examples of the shape of the silver powder are spherical and cubic or a combination thereof, or a combination of one or more thereof with other shapes. In one embodiment of the present invention, the silver powder in the conductive paste is spherical.
[0024] The particle size D50 is a particle characteristic known to those skilled in the art. The determination of the particle size D50 is known to those skilled in the art. According to the present invention, the particle size D50 of the silver powder is 0.1-3 μm, preferably 0.1-2 μm.
[0025] In one embodiment of the present invention, the silver powder is present in a proportion of 80-88 wt %, such as 85-88 wt %, of the conductive paste.
[0026] Glass powder composition
[0027] According to the present invention, glass powder is present in the conductive paste to cause etching. According to the present invention, a glass powder composition is used as the glass powder, and the glass powder composition comprises:
[0028] a) a first glass powder, and
[0029] b) a second glass powder,
[0030] wherein the first glass powder comprises 2-9 wt % of alkali metal oxide, 1-5 wt % of SiO2, 8-20 wt % of Bi2O3, 25-50 wt % of TeO2, 20-45 wt % of PbO, 0-10 wt % of WO3, 0-5 wt % of MoO3 and 0-5 wt % of ZnO, wherein the weight percentages are based on the total weight of all compounds in the first glass powder; and
[0031] The second glass powder contains 5-15 weight % of alkali metal oxides, 5-12 weight % of SiO2, 8-20 weight % of Bi2O3, 20-40 weight % of TeO2, 20-40 weight % of PbO, 0.1-7 weight % of Ag2O, 0.1-7 weight % of lanthanide compounds, 0-10 weight % of WO3, 0-5 weight % of MoO3 and 0-5 weight % of ZnO, wherein the weight percentages are based on the total weight of all compounds in the second glass powder.
[0032] In some embodiments, the first glass frit includes 2-9 wt %, eg, 3-5 wt %, or 6-8 wt % of an alkali metal oxide.
[0033] In some embodiments, the first glass frit includes 1-5 wt %, eg, 2-4 wt %, SiO 2 .
[0034] In some embodiments, the first glass frit includes 8-20 wt %, eg, 8-12 wt % or 13-18 wt % Bi 2 O 3 .
[0035] In some embodiments, the first glass frit includes 25-50 wt %, eg, 25-32 wt %, or 35-45 wt % TeO 2 .
[0036] In some embodiments, the first glass frit includes 20-45 wt %, eg, 25-32 wt %, or 33-40 wt % PbO.
[0037] In some embodiments, the first glass frit includes 0-10 wt %, eg, 1-10 wt % or 3-8 wt % WO 3 .
[0038] In some embodiments, the first glass frit includes 0-5 wt %, such as 1-5 wt %, of MoO 3 .
[0039] In some embodiments, the first glass frit includes 0-5 wt %, such as 1-5 wt %, ZnO.
[0040] In some embodiments, the second glass frit includes 5-15 wt %, such as 5-10 wt %, of an alkali metal oxide.
[0041] In some embodiments, the second glass frit includes 5-12 wt %, eg, 7-11 wt %, SiO 2 .
[0042] In some embodiments, the second glass frit includes 8-20 wt %, eg, 12-18 wt %, Bi2O3.
[0043] In some embodiments, the second glass frit includes 20-40 wt %, eg, 25-35 wt %, TeO 2 .
[0044] In some embodiments, the second glass frit includes 20-40 wt %, such as 20-30 wt %, of PbO.
[0045] In some embodiments, the second glass frit includes 0.1-7 wt %, such as 1-5 wt %, of Ag2O.
[0046] In some embodiments, the second glass frit includes 0.1-7 wt %, such as 1-5 wt %, of the lanthanide compound.
[0047] In some embodiments, the second glass frit includes 0-10 wt %, eg, 1-10 wt %, or 2-5 wt % WO 3 .
[0048] In some embodiments, the second glass frit includes 0-5 wt %, such as 1-5 wt %, of MoO 3 .
[0049] In some embodiments, the second glass frit includes 0-5 wt %, such as 1-5 wt %, ZnO.
[0050] In a preferred embodiment, the glass powder composition comprises:
[0051] a) a first glass powder, and
[0052] b) a second glass powder,
[0053] wherein the first glass powder comprises 2-9 wt % of alkali metal oxide, 1-5 wt % of SiO2, 8-20 wt % of Bi2O3, 25-50 wt % of TeO2, 20-45 wt % of PbO, 1-10 wt % of WO3, 1-5 wt % of MoO3 and 1-5 wt % of ZnO, wherein the weight percentages are based on the total weight of all compounds in the first glass powder; and
[0054] The second glass powder contains 5-15 weight % of alkali metal oxides, 5-12 weight % of SiO2, 8-20 weight % of Bi2O3, 20-40 weight % of TeO2, 20-40 weight % of PbO, 0.1-7 weight % of Ag2O, 0.1-7 weight % of lanthanide compounds, 1-10 weight % of WO3, 1-5 weight % of MoO3 and 1-5 weight % of ZnO, wherein the weight percentages are based on the total weight of all compounds in the second glass powder.
[0055] In a more preferred embodiment, the glass powder composition comprises:
[0056] a) a first glass powder, and
[0057] b) a second glass powder,
[0058] wherein the first glass powder comprises 2-9 wt % of alkali metal oxide, 1-5 wt % of SiO2, 8-20 wt % of Bi2O3, 25-50 wt % of TeO2, 20-45 wt % of PbO, 1-10 wt % of WO3, 1-5 wt % of MoO3 and 1-5 wt % of ZnO, wherein the weight percentages are based on the total weight of all compounds in the first glass powder; and
[0059] The second glass powder contains 5-15 weight % of alkali metal oxides, 5-12 weight % of SiO2, 8-20 weight % of Bi2O3, 20-40 weight % of TeO2, 20-40 weight % of PbO, 1-7 weight % of Ag2O, 1-7 weight % of lanthanide compounds, 1-10 weight % of WO3, 1-5 weight % of MoO3 and 1-5 weight % of ZnO, wherein the weight percentages are based on the total weight of all compounds in the second glass powder.
[0060] According to the present invention, the lanthanide compound includes oxides or other compounds of elements selected from La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu.
[0061] In a preferred embodiment, the alkali metal oxide includes Li2O, Na2O and K2O.
[0062] In a preferred embodiment, the first glass powder has a flow point of 400-650°C and the second glass powder has a flow point of 650-900°C.
[0063] According to the invention, the glass powder particles can have various shapes, surface properties, sizes, and surface area to volume ratios. Many shapes of glass powder particles are known to those skilled in the art. Some examples are spherical, angular, elongated (rod-like or needle-like), and flat (flake-like). The glass powder particles can also be present as a combination of particles of different shapes. According to the invention, glass powder having a shape or a combination of shapes that facilitates favorable sintering, adhesion, electrical contact, and conductivity of the resulting electrode is preferred.
[0064] According to the present invention, the first glass powder and the second glass powder each independently have a particle size D50 of 0.1-5 μm, preferably 0.4-3 μm. The determination of the particle size D50 is well known to those skilled in the art.
[0065] In one embodiment of the present invention, the glass frit composition is present in a ratio of 3.5-6 wt % of the conductive paste.
[0066] In one embodiment of the present invention, the first glass powder of the present invention can be prepared by the following method: all components of the first glass powder are combined together and melted to obtain a glass frit, the glass frit is cold-rolled or water-quenched to obtain glass slag, and the glass slag is wet-milled and / or dry-milled and graded to obtain a first glass powder having a desired particle size.
[0067] In one embodiment of the present invention, the second glass powder of the present invention can be prepared by the following method: all components of the second glass powder are combined together and melted to obtain a glass frit, the glass frit is cold-rolled or water-quenched to obtain glass slag, and the glass slag is wet-ground and / or dry-ground and graded to obtain a second glass powder having a desired particle size.
[0068] Preferably, the “melting” is carried out by charging the components of the glass powder into a crucible, placing the crucible in a muffle furnace and melting at high temperature; the “cold rolling” is carried out by cold rolling the glass frit in a cold rolling mill; the “water quenching” is carried out by removing the glass frit from the muffle furnace and pouring it into a bucket filled with deionized water; and the “wet grinding and / or dry grinding and grading the glass slag” is carried out, for example, by grinding the glass slag into coarse powder using a ball mill, and then grinding the coarse powder using a jet mill and grading it.
[0069] In the above method, the temperature of the muffle furnace is high enough to melt the components of the glass powder, and the melting time is long enough to uniformly mix the components.
[0070] More preferably, in the preparation of the glass powder, the temperature of the muffle furnace is 800-1500° C., and the melting time is 15 to 60 minutes.
[0071] In one embodiment of the present invention, the glass frit composition of the present invention is prepared by mixing a first glass frit and a second glass frit.
[0072] In one embodiment of the present invention, the glass frit composition comprises 40-80 wt %, such as 60-80 wt %, of the first glass frit, the weight percentage being based on the total weight of the glass frit composition.
[0073] In one embodiment of the present invention, the glass frit composition comprises 20-60 wt %, such as 20-40 wt %, of the second glass frit, the weight percentage being based on the total weight of the glass frit composition.
[0074] In one embodiment of the present invention, the glass powder composition comprises:
[0075] a) 40-80 wt % of a first glass powder, and
[0076] b) 20-60 wt. % of a second glass powder,
[0077] The weight percentages are based on the total weight of the glass frit composition.
[0078] Organic carrier
[0079] In one embodiment of the present invention, the conductive paste comprises an organic vehicle commonly used in the art.Preferred organic vehicles are those that provide optimal stability of the ingredients within the conductive paste and impart viscosity to the conductive paste that allows for effective printability.
[0080] In one embodiment, the amount of the organic vehicle may be 6-15 wt %, such as 8-12 wt %, based on the total weight of the conductive paste.
[0081] In one embodiment, the organic vehicle comprises a solvent, a binder (e.g., an organic binder, such as a polymer, a resin), a surfactant, an additive, or any combination thereof, preferably an organic binder and a solvent. The additive comprises a film-forming aid (e.g., alcohol ester dodeca), a thixotropic agent, a viscosity regulator, a stabilizer, a thickener, an emulsifier, a dispersant, a slip agent (e.g., dimethicone), or a pH regulator, and any combination thereof. For example, in one embodiment, the organic vehicle comprises one or more binders in an organic solvent.
[0082] The binder can be present in an amount of 5-50 wt %, such as 10-45 wt % or 20-40 wt %, based on the total weight of the organic vehicle. Preferred binders are those that promote the formation of conductive pastes having favorable stability, printability, viscosity and sintering properties. Preferred binders (which generally fall within the category referred to as "resins") are polymeric binders, monomeric binders, and binders that are combinations of polymers and monomers. The polymeric binder can also be a copolymer.
[0083] Preferred polymeric binders include binders carrying functional groups in the polymer backbone, binders carrying functional groups outside the backbone, and binders carrying functional groups inside and outside the backbone. Preferred polymers carrying functional groups in the backbone include, for example, polyesters, substituted polyesters, polycarbonates, substituted polycarbonates, polymers carrying cyclic groups in the backbone, polysaccharides, substituted polysaccharides, polyurethanes, substituted polyurethanes, polyamides, substituted polyamides, phenolic resins, substituted phenolic resins, copolymers of one or more monomers of the above polymers (optionally with other comonomers) or combinations of at least two thereof.
[0084] Preferred polymers carrying cyclic groups in the main chain include, for example, polyvinyl butyral (PVB) and its derivatives and polyterpineol and its derivatives or mixtures thereof. Preferred polysaccharides include, for example, cellulose, methyl cellulose, ethyl cellulose, hydroxyethyl cellulose, propyl cellulose, hydroxypropyl cellulose, butyl cellulose, derivatives thereof and mixtures of at least two thereof. Other preferred polymers include, for example, cellulose ester resins, such as cellulose acetate propionate, cellulose acetate butyrate and any combination thereof. Other preferred polymers are those disclosed in U.S. Patent Application Publication No. 2013 / 0180583, which is incorporated herein by reference.
[0085] Preferred polymers carrying functional groups outside the polymer backbone are polymers carrying amide groups, polymers carrying acid and / or ester groups (commonly referred to as acrylic resins) or polymers carrying a combination of the above functional groups or a combination thereof. Preferred polymers carrying amide groups outside the backbone include, for example, polyvinyl pyrrolidone (PVP) and its derivatives. Preferred polymers carrying acid and / or ester groups outside the backbone include, for example, polyacrylic acid and its derivatives, polymethyl methacrylate (PMMA) and its derivatives or mixtures thereof.
[0086] Preferred monomeric binders include, for example, monomeric binders based on ethylene glycol. Preferred monomeric binders based on ethylene glycol are binders having multiple ether groups, multiple ester groups, or binders having one ether group and one ester group, preferred ether groups are methyl, ethyl, propyl, butyl, pentyl, hexyl and higher alkyl ethers, preferred ester groups are acetates and their alkyl ether derivatives, preferably ethylene glycol monobutyl ether monoacetate or mixtures thereof.
[0087] Preferred binders in the present invention are, for example, alkylcelluloses (preferably ethylcellulose), derivatives thereof and mixtures thereof with other binders from the previous list of binders.
[0088] The amount of the organic solvent may be 40-90 wt %, such as 35-85 wt %, based on the total weight of the organic vehicle.
[0089] Preferred solvents are those which allow the formation of an electroconductive paste having advantageous viscosity, printability, stability and sintering properties. All solvents known in the art and considered suitable in the present invention can be used as solvents in the organic vehicle. According to the present invention, preferred solvents are those which allow a preferred high level of printability of the electroconductive paste as described above to be achieved. Preferred solvents according to the present invention are solvents which are present in liquid form at standard ambient temperature and pressure (SATP) (25° C., 100 kPa).
[0090] Preferred solvents are polar or nonpolar, protic or aprotic, aromatic or nonaromatic. Preferred solvents include, for example, monoalcohols, diols, polyols, monoesters, diesters, polyesters, monoethers, diethers, polyethers, solvents comprising at least one or more of these classes of functional groups, optionally comprising other classes of functional groups, and mixtures of two or more of the above solvents, for example, diethylene glycol butyl ether acetate.
[0091] The organic vehicle may also include a surfactant. The amount of the surfactant may be 0.01-10 wt %, such as 0.1-8 wt % or 1-6 wt %, based on the total weight of the organic vehicle. Preferred surfactants in the present invention are surfactants that promote the formation of conductive pastes with favorable stability, printability, viscosity and sintering properties. All surfactants known in the art and considered suitable in the present invention may be used as surfactants in the organic vehicle. Preferred surfactants may have nonionic, anionic, cationic, amphoteric or zwitterionic heads. Preferred surfactants are polymeric and monomeric or mixtures thereof.
[0092] According to the present invention, the conductive paste optionally contains additives commonly used in the art. The amount of the additive can be 1-15% by weight, such as 5-10% by weight, based on the total weight of the organic vehicle. Preferred conductive paste additives are components added to the conductive paste in addition to the ingredients that have been explicitly mentioned, which are used to promote higher performance of the conductive paste, the electrode made therefrom, or the resulting crystalline silicon solar cell. All additives known in the art and considered applicable in the present invention can be used as conductive paste additives. Preferred additives are film-forming aids, thixotropic agents, viscosity regulators, stabilizers, thickeners, emulsifiers, dispersants, lubricants or pH regulators and any combination thereof. Preferred thixotropic agents herein are carboxylic acid derivatives, preferably fatty acid derivatives or combinations thereof. Preferred fatty acid derivatives are C9H 19 COOH (decanoic acid), C 11 H 23 COOH (lauric acid), C 13 H 27 COOH (myristic acid), C 15 H 31 COOH (palmitic acid), C 17 H35 COOH(stearic acid), C 18 H 34 O2(oleic acid), C 18 H 32 O2 (linoleic acid), castor oil, hydrogenated castor oil or a combination thereof. The preferred film-forming aid herein is alcohol ester dodeca. The preferred lubricant herein is dimethyl silicone oil.
[0093] Preparation of conductive paste
[0094] In one embodiment of the present invention, to form a conductive paste, glass powder, silver powder, organic vehicle, and optional conductive paste additives can be combined using any method known in the art for preparing a paste. The components can be mixed, for example, with a mixer, and then passed through, for example, a three-roll mill to make a dispersed uniform paste.
[0095] In one embodiment of the present invention, in order to form a conductive paste, a glass powder composition is mixed with an organic vehicle to obtain a glass paste, and the glass paste is mixed with other raw materials for forming a conductive paste (silver powder and optional conductive paste additives) to obtain a conductive paste.
[0096] In a preferred embodiment, in order to form a conductive paste, the first glass powder and the second glass powder are first mixed to obtain a glass powder blend, and then the glass powder blend is mixed with an organic vehicle to obtain a glass paste, and then silver powder is mixed with the obtained glass paste and an optional conductive paste additive to obtain a conductive paste.
[0097] Electrode for crystalline silicon solar cell and preparation method thereof
[0098] The method for preparing an electrode for a crystalline silicon solar cell of the present invention comprises applying a conductive paste on a substrate and performing a sintering process, wherein the sintering process is performed in a conventional manner well known to those skilled in the art.
[0099] In one embodiment of the present invention, the temperature of the conductive paste sintering treatment is 650-800°C, preferably 650-750°C.
[0100] In one embodiment of the present invention, the obtained electrode is a back P-region electrode of a crystalline silicon solar cell.
[0101] Crystalline silicon solar cells
[0102] The present invention also relates to a crystalline silicon solar cell, which comprises a substrate and the electrode combined on the substrate.
[0103] In one embodiment of the present invention, the crystalline silicon solar cell is a TBC solar cell.
[0104] In one embodiment of the present invention, the preferred crystalline silicon solar cell according to the present invention is a crystalline silicon solar cell with high efficiency in terms of the ratio of the total energy of the incident light converted to the electrical energy output. Lightweight and durable crystalline silicon solar cells are also preferred. Crystalline silicon solar cells may also include additional layers for chemical / mechanical protection.
[0105] In one embodiment of the present invention, the crystalline silicon solar cell substrate of the present invention is a substrate for crystalline silicon solar cells known to those skilled in the art.
[0106] The crystalline silicon solar cell of the present invention has an electrode formed by sintering the conductive paste of the present invention and bonded to the substrate.
[0107] In one embodiment of the present invention, the conductive paste of the present invention is applied to a substrate, such as a semiconductor substrate (eg, a crystalline silicon wafer), to form a printed electrode.
[0108] The conductive paste of the present invention can be applied to the substrate by any method known in the art and considered suitable in the present invention. Examples of such methods include, but are not limited to, dipping, impregnation, pouring, dripping, injection, spraying, blade coating, shower coating, brush coating or printing or a combination of at least two thereof. Preferably, the printing technique is inkjet printing, screen printing, flexographic printing, offset printing, relief printing or stencil printing or a combination of at least two thereof. It is preferred according to the present invention to apply the conductive paste of the present invention by printing, preferably by screen printing.
[0109] Firing is required to sinter the printed electrodes to form a solid conductor. Firing is well known in the art and may be achieved in any manner deemed appropriate in the present invention. It is preferred that firing is performed at a sintering temperature above 600°C.
[0110] In one embodiment of the invention, a passivation layer may be applied to the substrate, preferably the front and / or back of the crystalline silicon wafer as an outer layer. Preferably, the passivation layer is a passivation layer that reduces the electron / hole recombination rate near the electrode interface. Any passivation layer known in the art and considered to be applicable in the present invention may be used. According to the present invention, the passivation layer may be silicon nitride, aluminum oxide, silicon dioxide and titanium dioxide. According to a preferred embodiment, the passivation layer uses silicon nitride and aluminum oxide.
[0111] In one embodiment of the present invention, in addition to the above-mentioned layers which directly contribute to the main functions of the crystalline silicon solar cell, further layers may be added for mechanical and chemical protection.
[0112] The battery can be encapsulated to provide chemical protection. Encapsulation is well known in the art and any encapsulation suitable for the present invention can be used. According to a preferred embodiment, a transparent polymer (commonly referred to as a transparent thermoplastic resin) is used as an encapsulation material, provided that such an encapsulation exists. Preferred transparent polymers herein are silicone rubber and polyethylene vinyl acetate (EVA).
[0113] A transparent glass sheet may also be added to the front side of the crystalline silicon solar cell to provide mechanical protection thereto. Transparent glass sheets are well known in the art, and any transparent glass sheet suitable for use in the present invention may be employed.
[0114] A back protective material can be added to the back of the crystalline silicon solar cell to provide mechanical protection. Back protective materials are well known in the art, and any back protective material deemed applicable in the present invention can be used. A preferred back protective material according to the present invention is a back protective material with good mechanical properties and weather resistance. A preferred back protective material according to the present invention is polyethylene terephthalate with a polyvinyl fluoride layer (e.g., a PTFE layer). It is preferred according to the present invention that the back protective material is present below the encapsulation layer (in the presence of a back protective layer and an encapsulation layer).
[0115] Frame materials may be added to the outside of the crystalline silicon solar cell to impart mechanical support. Frame materials are well known in the art and any frame material deemed suitable for use in the present invention may be employed. A preferred frame structure according to the present invention is aluminum.
[0116] Those skilled in the art can more easily understand the present invention according to the following embodiments:
[0117] Embodiment 1. A glass powder composition comprising:
[0118] a) a first glass powder, and
[0119] b) a second glass powder,
[0120] wherein the first glass powder comprises 2-9 wt % of alkali metal oxide, 1-5 wt % of SiO2, 8-20 wt % of Bi2O3, 25-50 wt % of TeO2, 20-45 wt % of PbO, 0-10 wt % of WO3, 0-5 wt % of MoO3 and 0-5 wt % of ZnO, wherein the weight percentages are based on the total weight of all compounds in the first glass powder; and
[0121] The second glass powder contains 5-15 weight % of alkali metal oxides, 5-12 weight % of SiO2, 8-20 weight % of Bi2O3, 20-40 weight % of TeO2, 20-40 weight % of PbO, 0.1-7 weight % of Ag2O, 0.1-7 weight % of lanthanide compounds, 0-10 weight % of WO3, 0-5 weight % of MoO3 and 0-5 weight % of ZnO, wherein the weight percentages are based on the total weight of all compounds in the second glass powder.
[0122] Embodiment 2. A glass powder composition according to Embodiment 1, wherein the lanthanide compound comprises an oxide of an element selected from La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu.
[0123] Embodiment 3. The glass frit composition according to Embodiment 1 or 2, wherein the alkali metal oxide comprises Li2O, Na2O and K2O.
[0124] Embodiment 4. A glass powder composition according to any one of Embodiments 1-3, wherein the first glass powder comprises 1-10 wt.% WO3, 1-5 wt.% MoO3 and 1-5 wt.% ZnO.
[0125] Embodiment 5. The glass powder composition according to any one of Embodiments 1-4, wherein the second glass powder comprises 1-10 wt.% WO3, 1-5 wt.% MoO3 and 1-5 wt.% ZnO.
[0126] Embodiment 6. The glass powder composition according to any one of Embodiments 1 to 5, wherein the first glass powder and the second glass powder each independently have a particle size D50 of 0.1-5 μm, preferably 0.4-3 μm.
[0127] Embodiment 7. The glass frit composition of any one of Embodiments 1-6, wherein the first glass frit has a flow point of 400-650°C and the second glass frit has a flow point of 650-900°C.
[0128] Embodiment 8. The glass powder composition according to any one of Embodiments 1-7, wherein the glass powder composition comprises:
[0129] a) 40-80 wt % of a first glass powder, and
[0130] b) 20-60 wt. % of a second glass powder,
[0131] The weight percentages are based on the total weight of the glass frit composition.
[0132] Embodiment 9. A conductive paste for p+poly silicon in a TBC cell, comprising: 80-88 wt % of silver powder, 3.5-6 wt % of the glass powder composition according to any one of Embodiments 1-8, and 6-15 wt % of an organic vehicle.
[0133] Embodiment 10. The conductive paste according to embodiment 9, wherein the silver powder has a particle size D50 of 0.1-3 μm, preferably 0.1-2 μm.
[0134] Embodiment 11. The electroconductive paste according to embodiment 9 or 10, wherein the electroconductive paste does not contain aluminum.
[0135] Embodiment 12. A method for preparing the conductive paste described in any one of Embodiments 9-11, the method comprising mixing a glass powder composition with an organic carrier to obtain a glass paste, and mixing the glass paste with other raw materials for forming a conductive paste to obtain a conductive paste.
[0136] Embodiment 13. An electrode for a crystalline silicon solar cell, wherein the electrode is formed by sintering the conductive paste described in any one of Embodiments 9 to 11.
[0137] Embodiment 14. A crystalline silicon solar cell comprising a substrate and the electrode described in Embodiment 13 bonded to the substrate.
[0138] Embodiment 15. The crystalline silicon solar cell according to Embodiment 14, wherein the crystalline silicon solar cell is a TBC cell.
[0139] Example
[0140] The present invention is illustrated below by way of example, but it should be understood that the following examples are non-limiting and are not intended to limit the scope of protection of the present invention.
[0141] raw material
[0142] Li2O, SiO2, Bi2O3, TeO2, PbO, WO3, MoO3, ZnO, Ag2O, La2O3, CeO2, and Yb2O3 are 4N grade chemical reagents.
[0143] Silver powder (Ag) is a spherical powder with a particle size D50 of 2.0 μm.
[0144] The silicon wafer is a 182*182mm BC single crystal silicon wafer.
[0145] The organic carrier is composed as follows:
[0146] Saturated polyester resin with a molecular weight of 10,000 to 30,000: 2.0 wt%;
[0147] Polyvinyl butyral: 1.0 wt%;
[0148] Diethylene glycol butyl ether acetate: 4.8 wt%;
[0149] Alcohol ester twelve: 0.5 weight;
[0150] Dimethyl silicone oil: 0.2% by weight
[0151] The weight percentages are based on the weight of the conductive paste.
[0152] Test Method
[0153] In the present invention, the contact resistivity is tested by a contact resistance tester (TLM-SCAN from pv-tools) according to the transmission line model (TLM) method, and the contact resistance is calculated by measuring the relationship between current and voltage. The specific implementation method is as follows: first, the conductive paste is printed on the BC single crystal silicon wafer used to complete sintering. Afterwards, the gate line width and the gate line spacing are measured as input parameters, and the resistance of the gate line nodes after adjacent metallization at different spacings is measured by four probes, and the software calculates the contact resistance of the paste in the P region.
[0154] The metal composite in the present invention is to use photoluminescence (PL) to measure the difference between the dark saturation current density of the emission level passivation area and the dark saturation current density after metallization. The specific implementation method is as follows: first, the conductive paste is printed on the BC single crystal silicon wafer used and sintered. Then, the cell sample is photographed using a PL imager (Electric and Photoluminescence analyzer from IVT-Solar) to obtain a PL image, and the PL image is processed using image processing software to obtain a brightness value. The dark saturation current density difference corresponding to the brightness value of the passivation area and the metallization area can be calculated by software, which is the metal composite of the paste in the P area.
[0155] The flow point of the glass powder in the present invention is measured by a high temperature microscope (HSM) (EM301 Heating Microscope from Hesse Instruments), and the specific implementation method is as follows: the finished glass powder is added into a mold and pressed into a columnar shape, and the columnar sample is placed on an alumina sheet and placed on a high temperature microscope stand. The software automatically determines the flow point of the sample through the contraction and expansion of the sample during the heating process. The heating temperature range is room temperature to 800°C.
[0156] Preparation of glass powder
[0157] Weigh the substances listed in Table 1 and mix them evenly;
[0158] The mixed raw materials were placed in a platinum crucible and melted in a muffle furnace at 1100°C for 30 min;
[0159] Pour the glass frit into the cold rolling mill and quickly cool it to below 100°C to obtain glass slag;
[0160] Place the glass slag in a ball mill and grind it for 30 minutes to obtain coarse powder;
[0161] The coarse powder was ground with a jet mill and classified to obtain glass powders A1, A2, B1, B2, and B3, respectively.
[0162] Table 1 Composition of glass powder
[0163]
[0164]
[0165] Preparation of Conductive Paste (Examples 1-4 and Comparative Examples 1-4)
[0166] Silver powder, glass powder and organic carrier were weighed respectively according to the ratio shown in Table 2. The glass powder and the organic carrier were first mixed with a planetary mixer to obtain a glass paste. The obtained glass paste was then mixed with silver powder and then mixed with a three-roll grinder to obtain conductive pastes of Examples 1-4 and Comparative Examples 1-4.
[0167] Table 2 Composition of conductive paste
[0168] Conductive paste Silver powder (weight %) Glass powder (weight %) Organic carrier (wt%) Comparative Example 1 87% 5%A1 8% Comparative Example 2 87% 5%A2 8% Comparative Example 3 87% 5%B1 8% Comparative Example 4 87% 5%B3 8% Example 1 87% 4% A1+1% B1 8% Example 2 87% 3% A1+2% B3 8% Example 3 87% 4% A2+1% B2 8% Example 4 87% 2% A2+3% B3 8%
[0169] Preparation of solar cells with electrodes (Samples 1-4 of the present invention and comparative samples 1-4)
[0170] The conductive pastes of Examples 1-4 and Comparative Examples 1-4 were respectively printed on 182*182mm BC monocrystalline silicon wafers by screen printing (430-8-12-4-12um-9BB screen) to form fine grids on the back side (polished side). After all the grid lines were printed, they were dried and then rapidly sintered under the conditions of a peak temperature of 720°C and a time of 16 seconds from room temperature to the peak temperature to obtain solar cells with electrodes (Samples 1-4 of the present invention and Comparative Samples 1-4), and the contact resistance and metal composite performance were tested. The results are shown in Table 3.
[0171] Table 3 Contact resistance and metal composite performance of solar cells
[0172] Glass powder (weight %) <![CDATA[Contact resistivity (mΩ·cm 2 )]]> <![CDATA[Metal composite (fA / cm 2 )]]> Comparative sample 1 5%A1 1.5 2100 Comparative sample 2 5%A2 2.1 1600 Comparative sample 3 5%B1 3.2 500 Comparative sample 4 5%B3 8.3 300 Sample 1 of the present invention 4% A1+1% B1 1.2 1200 Sample 2 of the present invention 3% A1+2% B3 1.2 700 Sample 3 of the present invention 4% A2+1% B2 1.5 600 Sample 4 of the present invention 2% A2+3% B3 3.1 500
[0173] As can be seen from the results in Table 3, the samples of the present invention using the combination of two glass powders have achieved a good balance between contact resistance and metal composite performance compared to the comparative samples using the corresponding single glass powder. Specifically, the comparative sample 1 using glass powder A1 alone has a low contact resistance but poor metal composite performance, while the comparative sample 3 using glass powder B1 alone has a high contact resistance despite its good metal composite performance. On the contrary, the contact resistance of the sample 1 of the present invention using the combination of glass powders A1 and B1 is lower than that of the comparative sample 1 using glass powder A1 alone and the comparative sample 3 using glass powder B1 alone, and its metal composite performance is also acceptable, so the solar cell of the present invention has achieved a good balance between contact resistance and metal composite performance. Similarly, the samples 2-4 of the present invention using the combination of two glass powders have also achieved a good balance between contact resistance and metal composite performance compared to the comparative samples using the corresponding single glass powder, and in particular, the samples 2 and 3 of the present invention have achieved an excellent balance between contact resistance and metal composite performance.
[0174] Although specific embodiments of the present invention are shown and described, it should be understood that other improvements, substitutions and alternatives are known to those skilled in the art. Such improvements, substitutions and alternative embodiments may be made without departing from the spirit and scope of the present invention as determined by the appended claims. Each feature of the present invention is described in the appended claims.
Claims
1. A glass powder composition comprising: a) a first glass powder, and b) a second glass powder, wherein the first glass powder comprises 2-9 wt % of alkali metal oxide, 1-5 wt % of SiO2, 8-20 wt % of Bi2O3, 25-50 wt % of TeO2, 20-45 wt % of PbO, 0-10 wt % of WO3, 0-5 wt % of MoO3 and 0-5 wt % of ZnO, wherein the weight percentages are based on the total weight of all compounds in the first glass powder; and The second glass powder contains 5-15 weight % of alkali metal oxides, 5-12 weight % of SiO2, 8-20 weight % of Bi2O3, 20-40 weight % of TeO2, 20-40 weight % of PbO, 0.1-7 weight % of Ag2O, 0.1-7 weight % of lanthanide compounds, 0-10 weight % of WO3, 0-5 weight % of MoO3 and 0-5 weight % of ZnO, wherein the weight percentages are based on the total weight of all compounds in the second glass powder.
2. The glass powder composition according to claim 1, wherein the lanthanide compound comprises an oxide of an element selected from La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu.
3. The glass frit composition according to claim 1 or 2, wherein the alkali metal oxide comprises Li2O, Na2O and K2O.
4. The glass powder composition according to any one of claims 1 to 3, wherein the first glass powder comprises 1-10 wt% of WO3, 1-5 wt% of MoO3 and 1-5 wt% of ZnO.
5. The glass frit composition according to any one of claims 1 to 4, wherein the second glass frit comprises 1-10 wt% of WO3, 1-5 wt% of MoO3 and 1-5 wt% of ZnO. 6 . The glass powder composition according to claim 1 , wherein the first glass powder and the second glass powder each independently have a particle size D50 of 0.1-5 μm, preferably 0.4-3 μm.
7. The glass frit composition according to any one of claims 1 to 6, wherein the first glass frit has a flow point of 400-650°C and the second glass frit has a flow point of 650-900°C.
8. The glass powder composition according to any one of claims 1 to 7, wherein the glass powder composition comprises: a) 40-80 wt % of a first glass powder, and b) 20-60 wt. % of a second glass powder, The weight percentages are based on the total weight of the glass frit composition.
9. A conductive paste for p+poly silicon in a TBC battery, comprising: 80-88 wt % silver powder, 3.5-6 wt % of the glass powder composition according to any one of claims 1-8, and 6-15 wt % of an organic vehicle. 10 . The conductive paste according to claim 9 , wherein the silver powder has a particle size D50 of 0.1-3 μm, preferably 0.1-2 μm.
11. The conductive paste according to claim 9 or 10, wherein the conductive paste does not contain aluminum.
12. A method for preparing the conductive paste according to any one of claims 9 to 11, the method comprising mixing a glass powder composition with an organic vehicle to obtain a glass paste, and mixing the glass paste with other raw materials for forming a conductive paste to obtain a conductive paste.
13. An electrode for a crystalline silicon solar cell, the electrode being formed by sintering the conductive paste according to any one of claims 9 to 11.
14. A crystalline silicon solar cell comprising a substrate and the electrode according to claim 13 bonded to the substrate. The crystalline silicon solar cell according to claim 14 , wherein the crystalline silicon solar cell is a TBC cell.
Citation Information
Patent Citations
Conductive paste for fine-line high-aspect-ratio screen printing in the manufacture of semiconductor devices
US20130180583A1
Cited By
Glass powder composition for improving oxidation resistance of base metal slurry and base metal conductive slurry
CN122464615A
Glass powder composition, and conductive paste comprising glass powder composition and preparation method therefor
WO2026103791A1